THE REFLECTIONS OF HENRI BERGSON’S TIME PHILOSOPHY IN WILLIAM FAULKNER AND AHMET HAMDI TANPINAR - Bülent Cercis TANRITANIR (Fırat University, 2019)
Technological and scientific developments in the 19th and 20th-century caused to redefine the terms such as metaphysic, entity, reality, and relativity. One of the terms is 'time' which is handled and redefined in this period. Henri Bergson (1859-1941) who influenced a lot of people with his studies and his time philosophy has an important position. Bergson explains the ‘time entity’ with the terms like pure time, homogeneous time- nonhomogenous time, internal time. He leads to question the traditional methods and to seek the new ways of narration methods. A lot of modernist authors in literature had been influenced by Bergson’s time philosophy and they gave great importance Bergson's time philosophy in their works. In this study, we analyze the influence of Bergson's time philosophy comparing, on William Faulkner (1897-1962) in modern American literature and Ahmet Hamdi Tanpınar (1901-1962) in 20th-century Turkish literature. The novels, Faulkner’s The Sound and The Fury (1929) and Tanpınar’s Huzur (1949); were researched and revealed characteristics of Bergson’s time philosophy and its innovations. Then the reflections of these innovations in Faulkner’s and Tanpınar’s novels which we chose as the subjects of our study were examined.